2017
DOI: 10.1253/circj.cj-17-0400
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress Using Pluripotent Stem Cells for Cardiac Regenerative Therapy

Abstract: Pluripotent stem cells (PSCs) have gained interest for cell-based regenerative therapies because of their capacity to differentiate into most somatic cell types, including cardiomyocytes. Remarkable progress in the generation of PSC-derived cardiomyocytes has been made in this decade, and recent preclinical transplantation studies using various animal models have provided proof-of-principle for their use in heart regeneration. However, several obstacles preclude their effective and safe clinical application fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The use of expandable human pluripotent stem cells (hPSCs) with their plasticity in response to developmental signals is a promising and logical choice for many disease therapies ( Carpenter et al., 2009 , Cheng et al., 2014 , Ichimura and Shiba, 2017 ) and for modeling monogenic diseases ( Ebert et al., 2009 , Shi et al., 2017 ). This includes making kidney cells to model ESKDs, or for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The use of expandable human pluripotent stem cells (hPSCs) with their plasticity in response to developmental signals is a promising and logical choice for many disease therapies ( Carpenter et al., 2009 , Cheng et al., 2014 , Ichimura and Shiba, 2017 ) and for modeling monogenic diseases ( Ebert et al., 2009 , Shi et al., 2017 ). This includes making kidney cells to model ESKDs, or for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the following phase, cardiac specification and maturation are driven by Dickkopf and Noggin—antagonists of the WNT and BMP pathways, respectively. Also, various well-characterised small-molecule compounds can be employed to imitate cellular responses to naturally occurring protein ligands involved in the aforementioned signalling pathways 2 4 . 12-O-Tetradecanoylphorbol-13-acetate (TPA) is a very potent small-molecule compound.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical researches are underway in the field of cardiac regenerative medicine utilizing pluripotent stem cell-derived cardiomyocytes, and the presence of a percentage of cTnT-negative cells in the cell population prepared for clinical studies was reported, underscoring the importance of purity control 24 . In the realm of regenerative medicine, preference is given to methods that minimize the likelihood of causing genomic alterations, such as those employing episomal vectors 25 . One commonly employed selection technique, which does not involve genetic modification, is the use of a glucose-free medium 10 .…”
Section: Discussionmentioning
confidence: 99%